2003
DOI: 10.1038/sj.npp.1300257
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 (MDR1)-Type P-Glycoproteins at the Blood–Brain Barrier Modulate the Activity of the Hypothalamic–Pituitary–Adrenocortical System: Implications for Affective Disorder

Abstract: Multidrug-resistance gene 1-type P-glycoproteins (ABCB1-type P-gps) protect the brain against the accumulation of many toxic xenobiotics and drugs. We recently could show that the access of the endogenous glucocorticoids corticosterone and cortisol to the brain are regulated by ABCB1-type P-gps in vivo. ABCB1-type P-gp function, therefore, is likely to exert a profound influence on the regulation of the hypothalamic-pituitary-adrenocortical (HPA) system. Hyperactivity of the HPA system is frequently observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 60 publications
4
70
0
Order By: Relevance
“…Moreover, we find that desipramine reduces MDR PGP (Mdr1a) expression in the hippocampus of FVB/N control controls, again consistent with previous work in cell lines (Varga et al, 1996;Szabo et al, 1999;Weiss et al, 2003;Pariante et al, 2003b;Weber et al, 2005). Finally, we replicate the previous finding by Muller et al (2003) showing that abcb1ab (À/À) mice have lower corticosterone levels than FVB/N controls. Indeed, desipramine treatment (in our model, a pharmacological 'knockdown' of MDR PGP) also lowers plasma corticosterone levels in controls, to levels indistinguishable from abcb1ab (À/À) mice.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, we find that desipramine reduces MDR PGP (Mdr1a) expression in the hippocampus of FVB/N control controls, again consistent with previous work in cell lines (Varga et al, 1996;Szabo et al, 1999;Weiss et al, 2003;Pariante et al, 2003b;Weber et al, 2005). Finally, we replicate the previous finding by Muller et al (2003) showing that abcb1ab (À/À) mice have lower corticosterone levels than FVB/N controls. Indeed, desipramine treatment (in our model, a pharmacological 'knockdown' of MDR PGP) also lowers plasma corticosterone levels in controls, to levels indistinguishable from abcb1ab (À/À) mice.…”
Section: Discussionsupporting
confidence: 92%
“…Post hoc analyses showed that untreated abcb1ab (À/À) mice had lower corticosterone levels than untreated FVB/N mice (gray column on the right vs gray column on the left; p ¼ 0.02); this replicates the findings by Muller et al (2003). It is also of note that there was an increase of corticosterone levels in saline-treated abcb1ab (À/À) mice compared with untreated abcb1ab (À/À) mice (gray vs white columns on the right; p ¼ 0.053), whereas the same phenomenon did not occur in FVB/N controls (gray vs white columns on the left; p ¼ 0.7).…”
Section: Effects Of Desipramine On Plasma Corticosterone Levelssupporting
confidence: 75%
See 3 more Smart Citations